CHRONIC TOPHACEUS GOUTY ARTHRITIS RESEMBLING RHEUMATOID ARTHRITIS - Nurdan Kotevoğlu; Beril Özcan; Banu Kuran (Archives of Rheumatology, 2003)
Chronic gouty arhritis with polyarticular type may mimic clinical presentation of rheumatoid arthritis. The coexistence of these two diseases was reported in previous case studies. Correct diagnosis can be reached through careful and detailed history taking, assessing tophus, evaluating radiological and laboratory findings; besides identification of monosodium urate crystals in the synovial or subcutaneous tissue. We aimed to discuss fourty-eight years old male patient, who had joint complaints for years and being treated as rheumatoid arthritis and later diagnosed as polyarticular gouty arthritis under the light of these information.